The effect of three levels of potassium and the dates of planting seedlings in the field on the yield, growth and quality of the stevia crop. - salman, moamer; Al-Taher, Faisal (University of Thi-Qar Journal of agricultural research, 2024)
A field experiment was conducted in an organic fertilizer preparation project located in Shatra District, which is 45 km north of Dhi Qar Governorate, during the 2022-2023 agricultural season, to study the effect of seedling planting dates (the first date is 1/12, the second date is 12/15, the third date is 12/30, the fourth date is 1/15, and the fifth date is 1/30), and levels of potassium fertilization (0, 25, 50 and 75 kg K ha-1). As for the interaction between them in terms of the growth, yield, and quality of the stevia crop, the experiment was carried out in accordance with a randomized complete block design (RCBD), with a split plot design, and with three replications. In the primary panels, the dates for planting seedlings were determined, and the levels of potassium fertilization in the secondary plots were determined. The results showed that the first date (1/12) recorded a significant increase in the leaf area , the total yield of dry leaves of the plant and plant height compared to the comparison treatment, as their averages reached 97.0 and 217.4 plant -1 dc for the two mowing , 25.81 megagrams ha-1 and 104.72 cm, in the sequence. While the increase in potassium levels led to a significant increase in most of the studied traits, compared to the control treatment, the K3 fertilizer level (75 kg potassium ha-1) recorded a noticeable increase in both the leaf area trait of the plant , the chlorophyll index, plant height and number of main branches, the average of which reached 194.9 plant dc-1. And 21.42 spad,92.76 cm and 8.61branches per plant-1 for the second mowing in the sequence, the above fertilizer level also gave a significant increase in Rebaudioside A, which averaged 136.65 and 132.35, in the sequence, for both mowings. as for the effect of the interaction between potassium levels and dates, the combination treatment was superior to D1K1 (25 kg. Potassium h-1 with the first date D1 1/12), D5K2 (50 kg. Potassium ha-1 and the fifth date D5 30/1) and D4K3 (75 Kg. Potassium H-1 and the fourth date D4 15/1) in leaf area, chlorophyll index, potassium content of leaves, and total yield of dry leaves, which amounted to 111.5 plant fat-1, 31.79 spores, 20.12 µg/g, and 28.94 µg/h. -1 for the first mowing in the sequence.